Perspective of drip irrigation in temperate fruits in India – A review - VERMA, PRAMOD; CHANDEL, J. S.; SHARMA, N. C. (Journal of Soil and Water Conservation, 2020)
Increasing water demand in various sectors and inefficient water uses especially in agriculture, pose huge challenges in future water availability. Therefore, the future is seeking a more efficient method of water use in country like India. Drip irrigation is the most efficient method of irrigation especially in fruit crops, in which frequent application of water is given directly on or below the soil surface nearby the root zone of plants. Drip irrigation aims at increasing physiological growth, yield, quality, wateruse- efficiency and saved water use in fruit crops as compared to conventional method of irrigations. In this article, the investigational evidence reported on drip irrigation, its application in different temperate fruit crops and its comparison with other irrigation method has been reviewed and discussed in order to meet the definite perception for the benefit of farmer community.